Daya Saing dan Determinan Ekspor Crude Palm Oil (CPO) Indonesia dalam Perspektif Lingkungan Berkelanjutan - Luthfi Fa'izah, Raihanah; Prasetyo, P. Eko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Crude Palm Oil (CPO) is one of the commodities that plays an important role in driving national economic growth. Indonesia holds the position of the world's largest CPO exporting country. This research aims to identify the level of competitiveness and analyze the determinants influencing Indonesian CPO commodity exports in the international market. This research uses time series data from the period 1989–2023. Competitiveness is measured using the Revealed Comparative Advantage (RCA) approach, while the analysis of factors influencing CPO exports is conducted using multiple linear regression with STATA software version 17. The data used in this study is secondary, obtained from various official sources such as the Central Bureau of Statistics (BPS), UN Comtrade, the World Bank, Index Mundi, and other relevant scientific literature. The analysis results show that the RCA value of Indonesian CPO throughout the period 1989–2023 is above one, indicating that this commodity has a comparative advantage in the international market. Furthermore, the variables of carbon dioxide (CO₂) emissions, the international price of CPO, and the Roundtable on Sustainable Palm Oil (RSPO) policy were proven to have a positive and significant influence on the export value of Indonesian CPO. Conversely, the domestic inflation rate had a negative impact on CPO exports.